Hemingway and Malraux: The Unmanned Virile Fraternity - Harris, Geoffrey (Miscelánea: A Journal of English and American Studies, 1999)
This essay initially draws on the feminist criticism of Gilbert and Gubar,Ppykett, Bonnie Kime Scott and Elaine Showalter to underline the theme of male inadequacy in the early work of Hemingway and Malraux, two of the most "masculine" of modernist novelists. In the aftermath of the First World War a certain concept of masculinity becomes irrelevant and the fictional virile hero finds himself involved in shifting gender boundaries. Harris takes issue, however, with the same feminist theorists when they maintain that this process resulted in the empowerment of women. Close textual and thematic analysis of a number of works shows that while the dislocation caused by the war may have unmanned the virile hero, it does not lead to the enabling of the figure of the heroine. If female characters move into the vacuum left by the beleaguered virile fraternity, they also inherit man's newfound vulnerability. The focus on the umanned hero does not contribute to any concept of the New Woman and the demise of the male hero is not a t consequence of the emergence of an authoritarian heroine. The virile fraternity is solely responsible for its own dislocation.